(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education is a pillar of developed and a powerful country, besides being the most important element for growth and prosperity of a nation, education gives knowledge and enlightenment which opens up new avenues of development of humanism and also transforms a human being into a wholesome noble soul and promotes universal brotherhood in its true senses. Today’s world is a world of information explosion. This information explosion is taking place at such a fast pace that even a literate person is feeling as if he or she is illiterate being not able to cope up with such an information explosion. Technology, in this regard, is one of the most critical issues in the present global era. In order to gain a broad perspective, yet remain relevant to one’s own situation, now there is a need to think globally and act locally. Technology means scientific principles applied to practical knowledge for obtaining the specific results. Technology in acquiring knowledge and skill is an extremely essential component of education and training at all levels primary, secondary, higher and professional education. Information Technology (IT) has a very important role to play as far as bringing transparency and accountability in the education system. In this article we will study about the meaning, role and importance of ICT in School Education and what are the importance and role of Student Information Management System and the significant role it plays for the students.